Snakebite envenoming in French Guiana: Assessment of the preclinical efficacy against the venom of Bothrops atrox of two polyspecific antivenoms. (15th January 2020) - Resiere, Dabor; Villalta, Mauren; Arias, Ana Silvia; Kallel, Hatem; Nèviére, Rémi; Vidal, Nicolas; Mehdaoui, Hossein; Gutiérrez, José María
Abstract: Snakebite envenoming is a relevant public health problem in French Guiana, and Bothrops atrox is responsible for the vast majority of envenomings in this overseas French territory. The preclinical efficacy of freeze-dried antivenoms manufactured in Costa Rica (Polival-ICP®) and Mexico (Antivipmyn Tri®) was assessed against the lethal, hemorrhagic, in vitro coagulant, and myotoxic effects of Bothrops atrox venom from French Guiana. Antivenoms differ in protein concentration and in the type of active principle (IgG and F (ab')2, respectively). Polival-ICP® showed significantly higher neutralizing activity against lethal, hemorrhagic and in vitro coagulant activities of the venom. Antivenoms neutralized myotoxic effect to a similar extent. In the case of lethal activity, Antivipmyn Tri® did not neutralize the effect at the highest antivenom level tested (1 mg venom/mL antivenom). Graphical abstract: Image 10573 Highlights: Polival-ICP and Antivipmyn Tri antivenoms were assessed against  Bothrops atrox  venom from French Guiana. Only Polival ICP neutralized the lethal activity of the venom. Both antivenoms neutralized hemorrhagic, in vitro coagulant and myotoxic effects of venom. Neutralizing potency against hemorrhagic and in vitro coagulant effects was higher for Polival-ICP antivenom.